Incidence of severe coronary stenosis in asymptomatic patients with peripheral arterial disease scheduled for major vascular surgery - Hromadka, Milan; Baxa, Jana; Seidlerova, Jitka; Suchy, David; Sedivy, Jakub; Stepankova, Lucie; Rajdl, Daniel; Rokyta, Richard (International angiology, 2016)
BACKGROUND: Peripheral arterial disease (PAD) has the risk equivalent of coronary heart disease. The biochemical parameters associated with functionally significant coronary artery stenosis were investigated in asymptomatic patients with PAD who were scheduled for major vascular intervention. METHODS: A total of 50 PAD patients asymptomatic for coronary heart disease were examined using coronary computed tomography angiography (CTA). A stress myocardial CT perfusion (CTP) test was performed in patients who exhibited coronary stenosis >40%. In patients with stress-induced perfusion defects, the severity of stenosis was assessed using invasive coronary angiography including fractional flow reserve assessment. The CT findings were correlated with both classical and more recently developed parameters of atherosclerosis. RESULTS: According to the combined CT examination (CTA and stress CT perfusion), 36% of patients exhibited significant coronary stenosis. Stress-induced hypoperfusion was observed in 95.7% of severe stenotic lesions. After adjustment for confounders, the level of high-sensitivity troponin I was associated with severe coronary stenosis (OR 1.260 [95% CI 1.054 to 1.505]). Other biochemical parameters did not correlate with coronary stenosis. The annual mortality rate was 4%. CONCLUSIONS: The results of the present study confirm a significant diagnostic contribution of a complex cardiac CT examination in patients scheduled for major vascular surgery. A high prevalence of asymptomatic coronary heart disease was observed in this particular patient group. High-sensitivity measurements of troponin I correlated with the extent of the coronary stenosis.
Keywords: Vascular Surgical Procedures; frakční průtoková rezerva myokardu; Appointments and Schedules; onemocnění periferních arterií; Humans; lidé středního věku; Coronary Stenosis; prevalence; Predictive Value of Tests; Female; Aged; komorbidita; senioři; schůzky a rozvrhy; lidé; Biomarkers; Computed Tomography Angiography; koronární stenóza; Troponin I; Peripheral Arterial Disease; koronární angiografie; biologické markery; ženské pohlaví; Male; výkony cévní chirurgie; Comorbidity; prediktivní hodnota testů; Middle Aged; incidence; Incidence; Czech Republic; Aged, 80 and over; troponin I; Coronary Angiography; Prevalence; senioři nad 80 let; Fractional Flow Reserve, Myocardial; Myocardial Perfusion Imaging; zobrazování myokardiální perfuze; Česká republika; mužské pohlaví; CT angiografie